2018
DOI: 10.1111/ecc.12916
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and satisfaction with intensive physiotherapy treatment during chemotherapy in patients with bone tumours and evaluation of related prognostic factors: An observational study

Abstract: The purpose of this study was to evaluate compliance and satisfaction of adult patients to intensive rehabilitation treatment during chemotherapy cycles after surgery for bone‐musculoskeletal tumours, as well as to identify possible predictive factors. An observational, prognostic, prospective study was conducted. The study enrolled 27 patients who previously had undergone modular knee prosthesis surgery in the period between October 2014 and October 2015. The outcome was compliance to intensive rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Included studies were published between January 2006 and April 2019 (Table 3 ). Five studies had a cross-sectional design [ 31 , 32 , 34 36 ], the remaining two articles were a clinical [ 33 ] and randomised controlled trial [ 37 ]. Three articles included a control group [ 33 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included studies were published between January 2006 and April 2019 (Table 3 ). Five studies had a cross-sectional design [ 31 , 32 , 34 36 ], the remaining two articles were a clinical [ 33 ] and randomised controlled trial [ 37 ]. Three articles included a control group [ 33 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up periods ranged from six weeks [ 34 ] to five years [ 36 ]. All articles reported functional performance outcome measures, of which MSTS was reported most frequently [ 32 36 ], followed by TESS [ 31 , 33 ], timed up-and-go (TUG) [ 31 , 33 ], 6-min walk test (6mWT) [ 31 , 33 ] 10-m walk test (10mWT) [ 33 ], Harris hip score (HHS) [ 34 ], a custom-made functional performance scoring system [ 34 ], gait evaluation (including walking speed) [ 36 ], the hospital for special surgery (HSS) knee score [ 37 ], and, last, the number of patients that had been out of their beds for the first time on the third, seventh, and fourteenth postoperative day [ 37 ]. Outcome measures in the category ‘Joint and muscle function’ were reported in four out of seven articles (57%), with knee ROM being reported most frequently [ 31 , 33 , 36 , 37 ], followed by quadriceps strength on the medical research council (MRC) scale [ 31 , 33 ] and isokinetic muscle strength [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compliance and satisfaction with intensive physiotherapy treatment during chemotherapy in patients with bone tumours and evaluation of related prognostic factors: An observational study done by MattiaMorri suggested it is a feasible treatment for bone tumour patients who have shown they can positively adhere to it [11,12]. Wiebke Jensen and team said in their research that physical exercise and therapy in terminally ill cancer patients will get help from physical exercises, relaxation therapy, and breathing training and these were the most commonly used modalities and it is more feasibility and acceptability [13,14]. Radiotherapy may cause malignant transformation so it is contraindicated in the management of the chondroblastoma [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that biophysical therapy can play an auxiliary role in chemotherapy. Morri M et al 32 demonstrated that beginning to strengthen physical therapy for patients with bone tumors in chemotherapy is a viable treatment option and rehabilitation should be promoted based on the level of satisfaction reported by the patient during chemotherapy. Carina V 33 found that the biophysical therapies may be another therapeutic effect besides OS surgery, radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%